A better way to... manage late presenting complications of temporomandibular joint prostheses. Issue 1 (January 2022) - Linden, John; Dunphy, Benjamin; Adly Ghaly, Ghaly
Abstract : Introduction : Within our centre, Temporomandibular joint (TMJ) prostheses have been provided in varying materials and designs over the years. Various patients have re-presented with various late complications of such surgery including limited mouth opening, facial pain, swelling, malocclusion and malpositioned components. This case series aims to discuss and illustrate the multidisciplinary approach to assessment, planning, and surgery for this cohort of patients. Methods : A Retrospective review of late TMJ protheses complications presenting within our centre has been undertaken. This includes multiple patient cases, with photographs, detailing the MDT planning, surgery and outcomes. Results : The most common presentation was pain and limited mouth opening or ankylosis. A total of twelve cases are included. Five cases were related to full metal prosthesis. Malposition of the condylar element was found in six other cases. Malocclusion was present in three cases. Some cases benefited from the removal of the joint alone, others a simultaneous further joint replacement and some with concurrent orthognathic surgery. Outcomes show reduction in pain and improvement in opening most notably. Conclusions : This case series evidences that complications of TMJ prostheses can present late and that such surgery carries many and significant risks. It highlights the adopted multidisciplinary team approach ensures that prostheses are appropriately designed and positioned correctly, whilst simultaneously addressing any gross occlusal abnormalities.